Wild boar as a potential reservoir of zoonotic tick-borne pathogens - Hrazdilová, Kristýna; Lesiczka, Paulina Maria; Bardoň, Jan; Vyroubalová, Šárka; Šimek, Bronislav; Zurek, Ludek; Modrý, David (Ticks and tick-borne diseases, 2021)
The wild boar (Sus scrofa) population has increased dramatically over the last decades throughout Europe and it has become a serious pest. In addition, the common habitat of wild boar and of the tick, Ixodes ricinus, indicates the potential of wild boar to play a role in epidemiology of epizootic and zoonotic tick-borne pathogens, including Anaplasma phagocytophilum. In Europe, epidemiological cycles and reservoirs of A. phagocytophilum, including its zoonotic haplotypes, are poorly understood. In this study, we focused on detection and further genetic characterization of A. phagocytophilum and piroplasmids in 550 wild boars from eleven districts of Moravia and Silesia in the Czech Republic. Using highly sensitive nested PCR targeting the groEL gene, the DNA of A. phagocytophilum was detected in 28 wild boars (5.1 %) representing six unique haplotypes. The dominant haplotype was found in 21 samples from 7 different districts. All detected haplotypes clustered in the largest clade representing the European ecotype I and the dominant haplotype fell to the subclade with the European human cases and strains from dogs and horses. Nested PCR targeting the variable region of the 18S rRNA gene of piroplasmids resulted in one positive sample with 99.8 % sequence identity to Babesia divergens. The presence of these two pathogens that are primarily circulated by I. ricinus confirms the local participation of wild boar in the host spectrum of this tick and warrants experimental studies to address wild boar as a reservoir of zoonotic haplotypes of A. phagocytophilum.
Keywords: Animals; babezióza; Zoonosis; anaplasmóza; Prevalence; Disease Reservoirs; Piroplasmida; Genes, Protozoan; Ixodesricinus; zdroje nemoci; Wild boar; Sus scrofa; bakteriální geny; prasata; Piroplasmids; Swine Diseases; Genetic Variation; prevalence; Babesiosis; nemoci prasat; Czech Republic; Swine; Anaplasma phagocytophilum; Anaplasmosis; protozoální geny; Česká republika; Genes, Bacterial; zvířata; genetická variace